Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament untuk Meningkatan Hasil Belajar Siswa Kelas VI pada Mata Pelajaran Matematika di SDN No.058/XI Koto Dumo - Zainal Abidin (Universitas Batanghari Jambi, 2018)
This study aims to improve the learning outcomes of sixth grade students at SDN. No. 058/XI Koto Dumo on mathematics subject, especially on integer operation material by using cooperative learning model of Teams Games Tournament type. This research is a classroom action research conducted in three cycles and each cycle is done with four activities, namely planning, implementation, observation, and reflection. This study was conducted from August to November of 2016. The study involved 16 sixth graders. Data were collected by observation and test. Data were analyzed by using descriptive analysis and simple statistical test. The results showed that the activities and learning outcomes of students before and after the given action (Cycle I, Cycle II, and Cycle III) improved. Thus, the use of cooperative learning model type Teams Games Tournament in SDN. No. 058/XI Koto Dumo can improve student learning outcomes in mathematics subjects, especially on the subject matter of integer counting operations.